Cultural Beliefs and Psychosocial Responses among Cervical Cancer Patients - Ida Maryati; Wilan Fitriana; Suryani Suryani; Taty Hernawaty; Syiffa Salsabila Rausanfikra; Tuti Pahria; Shurouq Ghalib Qadous (CV Media Inti Teknologi, 2026)
Background: Cervical cancer patients frequently experience psychosocial challenges that are influenced by sociocultural beliefs regarding illness and treatment.Aims: This study examined the association between cultural beliefs and psychosocial responses among cervical cancer patients.Methods: An observational cross-sectional study was conducted from January to April 2024 among 61 cervical cancer patients receiving treatment at Dr. Hasan Sadikin Hospital, Bandung, Indonesia. Participants were recruited using convenience sampling. Data collection was conducted using structured questionnaires designed to obtain participants' demographic characteristics, cultural beliefs, and psychosocial responses. Descriptive statistics and Spearman rank correlation analysis were performed to examine the relationship between cultural beliefs and psychosocial responses.Results: The mean cultural beliefs score was 1.11 (SD = 0.18), while the mean psychosocial response score was 1.39 (SD = 0.32). Spearman's rank correlation analysis identified a moderate, statistically significant positive association between cultural beliefs and psychosocial responses (r = 0.525, p < .001).Conclusion: Cultural beliefs were significantly associated with psychosocial responses among cervical cancer patients. Sociocultural considerations should be integrated into culturally responsive psychosocial support, nursing care, and community-based cervical cancer support initiatives.